Pengaruh Karakteristik Informasi Sistem Akuntansi Manajemen, Ketidakpastian Lingkungan, Dan Desentralisasi Terhadap Kinerja Manajerial Pada Hotel Di Kota Bengkulu - Diah Khairiyah; Ahmad Junaidi; Muhammad Yusuf (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to test whether Broad scope, Timelines, Aggregation, Integration, environmental uncertainty, and decentralization affect managerial performance.The sample in this study were 35 respondents consisting of 22 hotels selected based on certain criteria using purposive sampling. The type research is descriptive quantitative research to hypothesis testing. This research is included in the quantitative approach and the data used in this research are primary data. The data collection method was carried out using the questionnaire method. Data was collected by survey method by disturbing questionnaires directly. Furthermore data analysis was carried out using multiple linear regression analysis with the help of the SPSS version 18.0 Program. The results of this study indicate that study indicate that (1) Broad scope characteristics do not affect managerial performance, (2) Timeliness characteristics affect managerial performance, (3) Aggregation characteristics affect managerial performance, (4) Integration characteristics affect managerial performance, (5) The characteristics of environmental uncertainty have an effect on managerial performance, (6) the characteristics of decentralization have no effect on managerial performance, (7) the characteristics of management accounting information systems, environmental uncertainty and decentralization have an effect on managerial performance.